Pelatihan Berpikir Positif untuk Menurunkan Kecemasan Menghadapi Masa Bebas pada Anak di Lembaga Pembinaan Khusus Anak Kutoarjo - Lainatussyifa Zulni; Koentjoro Koentjoro (Gadjah Mada Journal of Professional Psychology (GamaJPP), 2017)
Anxiety against liberation is a feeling of fear and concern, felt by someone who underwent a period of custody and will undergo a period of free. This anxiety will make a person feeling ostracized, denied his presence, even humiliated or insulted. One of the factors that considered influential in the reduction of anxiety against liberation is positive thinking. The purpose of this study was to develops positive thinking training as an alternative to solving anxiety problems facing the anxiety against liberation in children at prison special for children. This experiment conducted with untreated control group design with pretest and posttest design. Quantitative data analysis is done through a mixed ANOVA statistical test to determine the effects of positive thinking training to the experimental group between before and after training. The results of this study are positive thinking training can reduce anxiety against liberation on children in prison.